Partial pancreas transplant: Experimental evaluation - Mate, Miguel; Ventura, Gustavo; Sanguinetti, Julio; Mesa Figueras, Guillermo (Cirugía del Uruguay, 1971)
A short history of pancreatic transplants is made, indicating material and methods employed and including an evaluation of this procedure. The practical value of parcial heterotopic pancreatic transplant is discussed, and technical and biological aspects thereof are analyzed.